Coronary artery and myocardial inflammatory reaction induced by intracoronary stent - Gomes,Walter J. (2002)
BACKGROUND: Intra-coronary stents have been extensively employed in percutaneous coronary revascularization. However, despite breakthroughs and developments associated to this new technology, novel complications and findings have emerged compelling the cardiac surgeon to cope with this new scenario. The presence of an intra-coronary foreign body (stent) might induce an inflammatory reaction carrying functional and structural repercussions of the coronary artery and surrounding cardiac muscle. METHOD:Patients, who had previously undergone stent implantation (6 to 18 months) and were submitted to coronary artery bypass surgery, had biopsies taken from the grafted coronary artery distal to the stent and from the adjacent muscle. The collected samples were processed and stained with hematoxylin-eosin and histologically studied. RESULTS:The histology of the coronary artery distal to the stent revealed chronic inflammatory processes and an intimal acute inflammatory infiltrate, with polymorphonuclear leukocytes even at long term follow-up, 12 months after stent implantation, disclosing an ongoing inflammatory process. The myocardium adjacent to the stent implantation site exhibited a significant chronic inflammatory infiltrate and fibrosis compatible with myocarditis. CONCLUSION:The presence of an intra-coronary stent induces an acute and chronic inflammatory reaction, even over the long term, with involvement of the distal coronary artery and surrounding myocardium. Further studies are necessary to assess the inflammatory process extension and its consequences.